Effects of low‐frequency pulsed electromagnetic fields on plateau frostbite healing in rats. Issue 6 (12th October 2016) - Jiao, Mingke; Lou, Lin; Jiao, lin; Hu, Jie; Zhang, Peng; Wang, Zhongming; Xu, Wenjuan; Geng, Xiliang; Song, Hongping
Abstract: Plateau frostbite (PF) treatments have remained a clinical challenge because this condition injures tissues in deep layers and affected tissues exhibit unique pathological characteristics. For instance, low‐frequency pulsed electromagnetic field (PEMF) can affect tissue restoration and penetrate tissues. Therefore, the effect of PEMF on PF healing should be investigated. This study aimed to evaluate the effects of low‐frequency PEMF on PF healing systematically. Ninety‐six Sprague‐Dawley rats were randomly and equally divided into three groups: normal control, partial thickness plateau frostbite (PTPF), and PTPF with low‐frequency PEMF exposure (PTPF + PEMF). PTPF wounds were induced in the dorsum of the rats. The PTPF + PEMF group was exposed to low‐frequency PEMF daily. During PF healing, wound microcirculation in each group was monitored through contrast ultrasonography. Wound appearance, histological observation, and wound tensile strength were also evaluated. Results showed that the rate of the microcirculation restoration of the PTPF + PEMF group was nearly 25% faster than that of the PTPF group, and wound appearance suggested that the healing of the PTPF group was slower than that of the PTPF + PEMF group. Histological observation revealed that PEMF accelerated the growth of different deep tissues, as confirmed by tensile strength examination. Low‐frequency PEMF could penetrate PF tissues, promote their restoration, and provide a beneficial effect on PF healing. Therefore, this technique may be a potential alternative to treat PF.